The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1097/hnp.0000000000000137
|View full text |Cite
|
Sign up to set email alerts
|

Does Telephone Follow-Up and Education Affect Self-Care and Metabolic Control in Diabetic Patients?

Abstract: The major goal of diabetes control is to assist patients to perform self-care and metabolic control. One possible way to achieve this goal is education and regular monitoring of patients by telephone. Thus, the present study was conducted with the aim of investigating the impact of education and telephone follow-up on self-care and metabolic control in diabetic patients. This experimental study was conducted at a hospital in the Central Anatolia region of Turkey, with 88 diabetic patients including 44 interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…Seventeen studies reported HBA1c levels (Aliha et al, 2013;Aytekin et al, 2016;Blackberry, 2013;Bond, 2007;Borhani et al, 2013;Elgaphar, 2017;Hansen et al, 2017;Crowley et al, 2013;Kotsani et al, 2018;Navicharern et al, 2009;Nesari et al, 2010;Odnoletkova et al, 2016;Piette et al, 2001;Piette, 2000;Wong, 2005;Solaiman, 2016;Zolfaghari et al, 2012), four studies reported BMI (Aliha et al, 2013;Odnoletkova et al, 2016), five studies reported fasting blood sugar (Aliha et al, 2013;Borhani et al, 2013;Elgaphar, 2017;Kotsani et al, 2018;Solaiman, 2016), and four studies reported total cholesterol (Aytekin, 2016;Blackberry, 2013;Odnoletkova et al, 2016;Solaiman, 2016). Some literature did not report HbA1c levels or complete data, and we excluded these documents (Tsaklis, Kotsa, Kotsani, & Kazakos, 2015;Young et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Seventeen studies reported HBA1c levels (Aliha et al, 2013;Aytekin et al, 2016;Blackberry, 2013;Bond, 2007;Borhani et al, 2013;Elgaphar, 2017;Hansen et al, 2017;Crowley et al, 2013;Kotsani et al, 2018;Navicharern et al, 2009;Nesari et al, 2010;Odnoletkova et al, 2016;Piette et al, 2001;Piette, 2000;Wong, 2005;Solaiman, 2016;Zolfaghari et al, 2012), four studies reported BMI (Aliha et al, 2013;Odnoletkova et al, 2016), five studies reported fasting blood sugar (Aliha et al, 2013;Borhani et al, 2013;Elgaphar, 2017;Kotsani et al, 2018;Solaiman, 2016), and four studies reported total cholesterol (Aytekin, 2016;Blackberry, 2013;Odnoletkova et al, 2016;Solaiman, 2016). Some literature did not report HbA1c levels or complete data, and we excluded these documents (Tsaklis, Kotsa, Kotsani, & Kazakos, 2015;Young et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Through reading the full papers, 17 studies (Aliha et al, 2013;Aytekin et al, 2016;Blackberry, 2013;Bond, 2007;Borhani et al, 2013;Elgaphar, 2017…”
Section: Re Sultsmentioning
confidence: 99%
See 3 more Smart Citations